2007
DOI: 10.4269/ajtmh.2007.77.228
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Maternal Peripheral Malaria Parasitemia in Central Mozambique

Abstract: Malaria infection during pregnancy (MiP) is heterogeneously distributed even in malaria-endemic countries. Program planners require data to facilitate identification of highest-priority populations for MiP control. Using data from two cross-sectional studies of 5,528 pregnant women in 8 neighboring sites in Mozambique, we described factors associated with maternal peripheral parasitemia by using logistic regression. Principal multivariate predictors of maternal peripheral parasitemia were gravidity (odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In all four countries, the risk of malaria was also found to be greatest among women in their first pregnancy, younger women, those presenting at an earlier gestational age, as well as those of lower SES, with these factors remaining associated with infection in multivariable analyses. These factors are consistent with results found in other seasonal, 18 , 28 , 29 as well as nonseasonal, settings such as Mozambique 30 and Gabon. 17 We also found that net use was not associated with prevalence, except in Ghana where nonusers had lower prevalence (potentially because current net use may be a marker of living in areas with higher biting rates, and consequently higher malaria risk).…”
Section: Discussionsupporting
confidence: 91%
“…In all four countries, the risk of malaria was also found to be greatest among women in their first pregnancy, younger women, those presenting at an earlier gestational age, as well as those of lower SES, with these factors remaining associated with infection in multivariable analyses. These factors are consistent with results found in other seasonal, 18 , 28 , 29 as well as nonseasonal, settings such as Mozambique 30 and Gabon. 17 We also found that net use was not associated with prevalence, except in Ghana where nonusers had lower prevalence (potentially because current net use may be a marker of living in areas with higher biting rates, and consequently higher malaria risk).…”
Section: Discussionsupporting
confidence: 91%
“…We have reported elsewhere that ITNs and SP appeared to contribute independently to the reduction of maternal malaria parasitemia, and that SP appeared to be effective even in HIVinfected study participants. 10 Birth weight data were only available for pregnancies terminating in an institutional delivery by July 2004. We acquired birth weight data on 2529 liveborn singleton infants and 71 pairs of liveborn twins.…”
Section: Lessons From the Fieldmentioning
confidence: 99%
“…Moreover, studies on acceptability of malaria preventive interventions often examine them in isolation from other interventions. Therefore there is a need to better understand women's perceptions, acceptability and adherence to these interventions when they are integrated with other health services offered to them, such as ANC services [5], [9].…”
Section: Introductionmentioning
confidence: 99%